“E o que foi pedo, vai dá bom” – o rap periférico de Fortaleza e as possibilidades de um ensino de história para o letramento racial - Sousa, André Isaac Santos de (2024)
This study proposes a reflection on the necessity and possibilities of racial literacy among students through the teaching of History, using the musical production of Rap from the outskirts of Fortaleza as an educational tool. Faced with students' difficulties in understanding their racial identity and the functioning of racism, the aim is to implement an effective formation of racial literacy in basic education. The research is based on the perception that many Afro-descendant students do not identify themselves as Black, while white students often analyze racism indifferently. The cultural production of Rap is seen as a way to address these issues in a meaningful way, promoting historical and ethnic awareness. The analysis of the lyrics and themes of the peripheral Rap of Fortaleza in the classroom seeks to promote racial literacy by exploring cultural resistance and positive construction of ethnic identity as a pedagogical tool. The research aims to contribute to a richer historical education in ethnic-racial issues, especially in a context where the Black population is significant, but cultural identification is still challenging. The study also seeks to understand how the study of Local History, in this context, can help address the limitations and challenges of implementing an anti-racist proposal using Rap in a school environment. The methodology includes Oral History to capture the experiences of teachers and students through interviews, songs, and the History of the Present Time to relate recent past with contemporary reflections. The final product will consist of racial literacy workshops and a small Rap festival at school, aiming to concretize the proposed strategies and promote historical and anti-racist awareness among students. We will analyze the workshops and the festival to have concrete indicators of the possibilities of racial literacy through the teaching of History and peripheral Rap from Fortaleza.